Design of suspension control system for bearingless induction motor using fuzzy-I controller - Qasim Kadhim Jasim; Mohammed Moanes E. Ali (Institute of Advanced Engineering and Science, 2023)
In the bearingless induction motor (BIM), the rotor of BIM is supported by the magnetic force, the radial position control technique is studied in this paper, an approximation and simplification are used to create a linearized model of suspension system. The objective of this paper is to design a control system that overcomes the limitations of the traditional controller and to improve the control performance and achieve high stability, even if it is exposed to external disturbance and internal disturbance (changes in load or speed). In order to solve this problem, the proposed controller is based on the fuzzy-I controller that combines the positive features of both fuzzy logic and the integration. In comparison with the conventional PID, the results show that the fuzzy-I controller reduces the peak-to-peak rotor deviation by 23% under effect of external disturbance force and 31% under effect of speed variation and 9% under effect of load variation.